Secondary damage and neuroinflammation in the spinal dorsal horn mediate post-thalamic hemorrhagic stroke pain hypersensitivity: SDF1-CXCR4 signaling mediation - Liang, Ting; Chen, Xue-Feng; Yang, Yan; Yang, Fei; Yu, Yang; Yang, Fan; Wang, Xiao-Liang; Wang, Jiang-Lin; Sun, Wei; Chen, Jun (Frontiers in Molecular Neuroscience, 2022)
Central post-stroke pain (CPSP) is an intractable neuropathic pain, which can be caused by primary lesion of central somatosensory system. It is also a common sequelae of the thalamic hemorrhagic stroke (THS). So far, the underlying mechanisms of CPSP remain largely unknown. Our previous studies have demonstrated that SDF1-CXCR4 signaling in the hemorrhagic region contributes to the maintenance of the THS pain hypersensitivity via mediation of the thalamic neuroinflammation. But whether the spinal dorsal horn, an initial point of spinothalamic tract (STT), suffers from retrograde axonal degeneration from the THS region is still unknown. In this study, neuronal degeneration and loss in the spinal dorsal horn were detected 7 days after the THS caused by intra-thalamic collagenase (ITC) injection by immunohistochemistry, TUNEL staining, electron microscopy, and extracellular multi-electrode array (MEA) recordings, suggesting the occurrence of secondary apoptosis and death of the STT projecting neuronal cell bodies following primary THS via retrograde axonal degeneration. This retrograde degeneration was accompanied by secondary neuroinflammation characterized by an activation of microglial and astrocytic cells and upregulation of SDF1-CXCR4 signaling in the spinal dorsal horn. As a consequence, central sensitization was detected by extracellular MEA recordings of the spinal dorsal horn neurons, characterized by hyperexcitability of both wide dynamic range and nociceptive specific neurons to suprathreshold mechanical stimuli. Finally, it was shown that suppression of spinal neuroinflammation by intrathecal administration of inhibitors of microglia (minocycline) and astrocytes (fluorocitrate) and antagonist of CXCR4 (AMD3100) could block the increase in expression levels of Iba-1, GFAP, SDF1, and CXCR4 proteins in the dorsal spinal cord and ameliorate the THS-induced bilateral mechanical pain hypersensitivity, implicating that, besides the primary damage at the thalamus, spinal secondary damage and neuroinflammation also play the important roles in maintaining the central post-THS pain hypersensitivity. In conclusion, secondary neuronal death and neuroinflammation in the spinal dorsal horn can be induced by primary thalamic neural damage via retrograde axonal degeneration process. SDF1-CXCR4 signaling is involved in the mediation of secondary spinal neuroinflammation and THS pain hypersensitivity. This finding would provide a new therapeutic target for treatment of CPSP at the spinal level.